Efektivitas Penggunakan Aplikasi Fotostation Dalam Proses Kerja Divisi Foto Harian Kompas - Firdaus, Adita Ahmad; Rusmana, Agus; Perdana, Fitri (PT. Kreasi Karya Majakata, 2025)
This study aims to analyze the effectiveness of the Fotostation application in supporting the digital photo management process within the photo division of Harian Kompas. In the context of modern journalism, managing large volumes of visual content requires a structured, fast, and accurate system. This research uses a qualitative descriptive approach, with data collected through observation and in-depth interviews with key personnel involved in the daily workflow of photo management. The findings show that Fotostation serves as the central tool for receiving, organizing, and archiving journalistic photos. The system enables real-time integration of visual assets, supports metadata indexing, and ensures that photo classification aligns with editorial standards. It also facilitates efficient long-term archiving and retrieval through its Archive and Inhouse features, allowing users to track usage and avoid redundancy in publication. Furthermore, the system plays a crucial role in protecting copyright by requiring proper attribution and ensuring that only verified content is used. While Fotostation significantly increases the speed and accuracy of editorial photo processing, the system still faces technical challenges, especially regarding performance under high-volume data loads. Nonetheless, the application has proven to enhance the overall effectiveness of the photo division’s workflow, making the management of digital photo assets more reliable, structured, and professionally accountable